Ensuring Reliable and Safe Operation of Trunk Diesel Engines of Marine Transport Vessels - Sagin, Sergii; Madey, Volodymyr; Sagin, Arsenii; Stoliaryk, Tymur; Fomin, Oleksij; Kučera, Pavel (MDPI, 2022)
In this study, a method for ensuring reliable and safe operation of marine trunk diesel engines is considered. The research was carried out on 5L23/30 MAN-B&W diesel engines of a Bulk Carrier class vessel. The objective of the study was to determine the effect of the structural characteristics of the oil layer (wetting angle and thickness) on the operational parameters of a marine diesel engine (compression pressure, concentration of nitrogen oxides in exhaust gases and temperature of exhaust gases after the cylinder) and performance characteristics of the oil (base number, wear and contaminant elements). It has been established that an increase in the degree of the contact angles of wetting and in the thickness of the oil layer improves the heat and power and environmental performance of a diesel engine. At the same time, the decrease in compression pressure in the cylinder slows down, the temperature of gases after the cylinder decreases, and the emission of nitrogen oxides with exhaust gases decreases. Also, it was found that wear of diesel parts and oil oxidation are reduced. The study confirms the possibility of improving the reliable and safe operation of trunk-type diesel engines of maritime vessels by effective control of variables relating to the characteristics of engine oil.

In this study, a method for ensuring reliable and safe operation of marine trunk diesel engines is considered. The research was carried out on 5L23/30 MAN-B&W diesel engines of a Bulk Carrier class vessel. The objective of the study was to determine the effect of the structural characteristics of the oil layer (wetting angle and thickness) on the operational parameters of a marine diesel engine (compression pressure, concentration of nitrogen oxides in exhaust gases and temperature of exhaust gases after the cylinder) and performance characteristics of the oil (base number, wear and contaminant elements). It has been established that an increase in the degree of the contact angles of wetting and in the thickness of the oil layer improves the heat and power and environmental performance of a diesel engine. At the same time, the decrease in compression pressure in the cylinder slows down, the temperature of gases after the cylinder decreases, and the emission of nitrogen oxides with exhaust gases decreases. Also, it was found that wear of diesel parts and oil oxidation are reduced. The study confirms the possibility of improving the reliable and safe operation of trunk-type diesel engines of maritime vessels by effective control of variables relating to the characteristics of engine oil.
Ensuring Reliable and Safe Operation of Trunk Diesel Engines of Marine Transport Vessels
Keywords: maritime transport; bulk carriers; diesel engine; circulation system; engine oil; wetting angle; compression pressure; nitrogen oxide emission; wear; oil oxidation; maritime transport; bulk carriers; diesel engine; circulation system; engine oil; wetting angle; compression pressure; nitrogen oxide emission; wear; oil oxidation